Association of Trends in Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Seroprevalence and State-Issued Nonpharmaceutical Interventions: United States, 1 August 2020 to 30 March 2021 . (10th June 2022) - Miller, Maureen J; Himschoot, Austin; Fitch, Natalie; Jawalkar, Sucheta; Freeman, Dane; Hilton, Charity; Berney, Kevin; Guy, Gery P; Benoit, Tina J; Clarke, Kristie E N; Busch, Michael P; Opsomer, Jean D; et al.
Abstract: Background: We assess if state-issued nonpharmaceutical interventions (NPIs) are associated with reduced rates of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection as measured through anti-nucleocapsid (anti-N) seroprevalence, a proxy for cumulative prior infection that distinguishes seropositivity from vaccination. Methods: Monthly anti-N seroprevalence during 1 August 2020 to 30 March 2021 was estimated using a nationwide blood donor serosurvey. Using multivariable logistic regression models, we measured the association of seropositivity and state-issued, county-specific NPIs for mask mandates, gathering bans, and bar closures. Results: Compared with individuals living in a county with all three NPIs in place, the odds of having anti-N antibodies were 2.2 (95% confidence interval [CI]: 2.0–2.3) times higher for people living in a county that did not have any of the 3 NPIs, 1.6 (95% CI: 1.5–1.7) times higher for people living in a county that only had a mask mandate and gathering ban policy, and 1.4 (95% CI: 1.3–1.5) times higher for people living in a county that had only a mask mandate. Conclusions: Consistent with studies assessing NPIs relative to COVID-19 incidence and mortality, the presence of NPIs were associated with lower SARS-CoV-2 seroprevalence indicating lower rates of cumulative infections. Multiple NPIs are likely more effective than single NPIs. Abstract : The presence of continuous state-issued nonpharmaceutical interventions (mask mandates, gathering bans, and bar closures) are associated with lower severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) incidence. The combined use of nonpharmaceutical intervention (NPI) and seroprevalence data can inform long-term strategic approaches to limiting disease transmission.